Heartbroken ebook A novel. - Unger, Lisa (2012)
A shattering thriller about three women, strangers, on a heart-wrenching collision course none of them could have seen coming. Long after anyone expected Kate to do anything with her life, she did. Using the journals left behind by her aunt and grandmother, she wrote a novel based on a very real generation-old love story that ended in tragedy. On the other side of town, Emily is about to set fire to her life. She’s in a dead-end job and is involved with the wrong man; she can feel herself being drawn into darkness, with horrific consequences. With nowhere to go, she finds herself on the run.  Without knowing each other, and with lives that couldn't be more different, Kate and Emily head to the same point on the map: Heart Island, an idyllic place in the middle of a lake in the Adirondacks, owned for generations by Birdie Burke's family. The harsh and unyielding Birdie is at one with this island, which has a terrifying history all its own. She, too, has consequences to face. Heartbroken is a tense, mesmerizing novel about the limits of dysfunctional families, of an island haunted by dark memories and restless ghosts, and of the all-too-real demons we must battle.  Wonderfully suspenseful, exquisitely crafted, and written with raw, emotional power, this is Lisa Unger at her very best. Praise for Heartbroken “Stellar. . . .  Heartbroken  should be on everyone’s summer to-read list.  For best results, read it alone on an island on a dark and stormy night.” — USA Today  (4 stars) “ Heartbroken  has all the makings of a high-wire thriller.  But it’s the twisted psyches of its main characters that really unsettle. . . . Unger expertly shows how quiet betrayals can rupture a life as deeply as an act of violence.” — People  (3 ½ stars) “A can’t-put-down thriller interlaced with insightful family drama and echoes of  Wuthering Heights .” —Family Circle “Lisa Unger is one of the few women to first break into the genre of thrillers, then to dominate it.” — Minneapolis Star Tribune “Lisa Unger masterfully writes of the joys and frustrations of family life in her latest novel. . . . What makes [it] shine is the struggle of multidimensional characters with issues that all of us face but sometimes don’t want to acknowledge.” — Associated Press